Decision support heart disease detection system using decision tree technique / Muhammad Adam Hasanuddin - Hasanuddin, Muhammad Adam (2017)
Decision tree classifier technique has been implemented in various field or research. In this project, it focuses on finding the probability of having the heart disease symptoms. Decision tree was implemented in the project because the technique is suitable to determine the probability of having heart disease based on the attributes. The prototype system gives prediction based on the rules created. The dataset is provided by a trusted website. Based on the interview done with the stakeholder, currently the clinic does not have a system to manage and gives prediction regarding heart disease. Plus, junior cardiologists are able to use the system as an educational tool about cardiology. System Development Life Cycle is used as the chosen methodology for this project. In the future, the system is able to be enhanced into mobile application where the user is able to use the system anywhere.